2020
DOI: 10.1186/s13068-020-01742-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided protein engineering increases enzymatic activities of the SGNH family esterases

Abstract: Background: Esterases and lipases hydrolyze short-chain esters and long-chain triglycerides, respectively, and therefore play essential roles in the synthesis and decomposition of ester bonds in the pharmaceutical and food industries. Many SGNH family esterases share high similarity in sequences. However, they have distinct enzymatic activities toward the same substrates. Due to a lack of structural information, the detailed catalytic mechanisms of these esterases remain barely investigated. Results: In this s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…However, previous studies have predominantly focused on the habitat-specific and biochemical properties of lipolytic enzymes such as extreme pH, unique temperature tolerance (i.e., hyperthermostability or cold adaptivity), tolerance against organic solvents, halotolerance, and catalytic efficiency. ,, These features confer marine-derived enzymes enormous potential in future industrial applications. Until recently, only a small number of structural studies concerning the marine microbial lipolytic enzymes have been conducted. , In addition, the functions of these enzymes and underlying structure-based molecular mechanisms remain poorly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have predominantly focused on the habitat-specific and biochemical properties of lipolytic enzymes such as extreme pH, unique temperature tolerance (i.e., hyperthermostability or cold adaptivity), tolerance against organic solvents, halotolerance, and catalytic efficiency. ,, These features confer marine-derived enzymes enormous potential in future industrial applications. Until recently, only a small number of structural studies concerning the marine microbial lipolytic enzymes have been conducted. , In addition, the functions of these enzymes and underlying structure-based molecular mechanisms remain poorly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced conformational heterogeneity and enhanced activity of the H37A variant in comparison to unaltered conformational heterogeneity and reduced activity of H37K render that the charged amino acid at position 37 of T7L is not suited for optimal stability–function characteristics. Along similar lines, Li et al reported that structure-guided engineering of a charge reversal amino acid substitution from Asp to Lys yielded a 20% increase in enzymatic activity of the CrmE 10 protein . In a nutshell, the study provided deeper molecular insights into the structure–dynamics–stability–function landscape of the engineered T7L-H37A variant, which can be applied to other family members of endolysins and other categories of enzymes involved in versatile biotechnological applications to enhance and/or regulate their stability and activity characteristics.…”
Section: Discussionmentioning
confidence: 83%
“…Along similar lines, Li et al reported that structure-guided engineering of a charge reversal amino acid substitution from Asp to Lys yielded a 20% increase in enzymatic activity of the CrmE 10 protein. 81 In a nutshell, the study provided deeper molecular insights into the structure−dynamics−stability− function landscape of the engineered T7L-H37A variant, which can be applied to other family members of endolysins and other categories of enzymes involved in versatile biotechnological applications to enhance and/or regulate their stability and activity characteristics.…”
Section: ■ Resultsmentioning
confidence: 99%
“…TEs are found in the NagB (TE1) and SGNH (TE3) folds. [110][111][112][113][114] In TE1, which also includes acyl-CoA transferases, we predict that the catalytic residues of a putative acetyl-CoA hydrolase from Porphyromonas givgivalis (2NVV) and a CoA transferase from P. aeruginosa (2G39) are Val259-Glu284-Asn337-Gly378 and Ile264-Glu288-Asn341-Gly382, respectively, based on those known from A. aceti AarCH6 structures (4EU3, 5DDK). 107,108 In TE3, comparison to available structures-E. coli tesA (e.g., 1IVN, 1JRL) 110 and Pseudoalteromonas estA (3HP4) 111 -reveals the likely catalytic residues for an E. coil TE (6LFB, 6LFC) and A. indicum AlinE4 esterase (6IQ9, 6IQA, 6IQB) are Ser10-Asp154-His157 and Ser13-Asp162-His165, respectively.…”
Section: Catalytic Residues and Mechanisms In Other Foldsmentioning
confidence: 99%
“…113 Other SGNH fold TEs, CrmE10 and AlinE4 were similarly susceptible to engineering for increased enzymatic activity. 114 Two families have the β-lactamase fold: TE23 and TE32. The structures in TE23 are significantly less well conserved than those in TE32.…”
Section: Catalytic Residues and Mechanisms In Other Foldsmentioning
confidence: 99%